Ring-opening polymerization-induced crystallization-driven self-assembly of poly-L-lactide-block-polyethylene glycol block copolymers (ROPI-CDSA) - Paul J. Hurst (Nature Portfolio, 2020)
A key challenge in the self-assembly of block copolymers is obtaining independent control over molecular structure and hierarchical structure in all dimensions using scalable one-pot chemistry. Here the authors show the ring opening polymerization-induced crystallization-driven self-assembly of poly-L-lactide-block-polyethylene glycol block copolymers into 1D, 2D and 3D nanostructures.